Peningkatan Hasil Belajar Kewirausahaan Dan Prakarya Melalui Cooperative Learning - Siti Alifah (Peneliti.net, 2019)
Entrepreneurship lessons and crafts are often overlooked. Subjects that are sometimes forgotten to be developed and integrated in other subjects. On the one hand, other subjects received attention, especially the subjects tested in the National Examination, such as mathematics, Indonesian, English and others. Attention in the area of ​​entrepreneurship lessons requires more attention, considering the nature of this lesson can instill independent values. This study aims to examine and apply the methods of cooperative learning in entrepreneurship and craft lessons. Research site at Alihsan High School, Bekasi. A sample of 30 classical students was conducted using the normality test and homogeneity test. The results of the study pointed out that the cooperative learning method can improve entrepreneurial learning outcomes and craftsmanship.